Association between Obesity and Cardiovascular Disease Risk Factors in Different Age Groups of Adolescents: An Analysis of Data from the Korean National Health and Nutritional Examination Survey - Joowon Lee; Seul Gi Cha; Jue Seong Lee; Susan Taejung Kim; Young Hwan Song (MDPI AG, 2023)
We investigated the association between obesity and cardiovascular disease risk factors (CVDRFs) in adolescents. We performed a cross-sectional study using the data from 8149 adolescents, aged 10-18 years, included in the Korean National Health and Nutrition Examination Survey (2011-2020). Using the body mass index, we defined "overweight" (≥85th to <95th percentile) and "obese" (≥95th percentile). We analyzed the associations between obesity and CVDRFs (high blood pressure, abnormal lipid profiles, and high fasting glucose levels) by sex and age groups (early [10-12 years], middle [13-15 years], and late [16-18 years] adolescence). When analyzing all the subjects, being overweight was correlated with high blood pressure and abnormal all-lipid profiles in boys and high triglyceride and low high-density lipoprotein cholesterol levels in girls, while obesity was associated with all CVDRFs in both boys and girls. Analyzing separately in the age subgroups, the correlation between obesity and CVDRFs tended to be shown earlier in boys than in girls, and obesity tended to be associated with CVDRFs earlier than being overweight. The association between obesity and CVDRFs may begin to be shown at different periods of youth, depending on the degree of obesity, CVDRF variables, and sex.